2013
DOI: 10.1271/bbb.120747
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tyrosine in the Brain and Serum of Mice by Orally Administering Dipeptide SY

Abstract: We examined the effect of orally administering L-Ser-L-Tyr (SY) dipeptide on the brain of a serine deficiency disease model mouse to attain the efficient delivery of L-Tyr and L-Ser into the mouse brain. Oral SY administration increased the L-Tyr level more efficiently than L-Tyr administration with the same intake dose, but did not significantly affect the L-Ser level when compared with L-Ser administration.Key words: brain; dipeptide; Phgdh; serine; tyrosine It is well established that dysregulation in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Furthermore, we recently demonstrated that oral ingestion of the dipeptide Ser-Tyr (SY) increases the Tyr content in several brain regions of adult mice more efficiently than administration of Tyr alone at the same intake dose. 8) SY is the most prevalent Tyr-containing dipeptide moiety in several soy proteins. 9) Indeed, SY and other Tyr-containing dipeptides can be detected in their free dipeptide form in the soy peptides used in our in vivo study.…”
Section: Soy Peptide Ingestion Augments the Synthesis And Metabolism mentioning
confidence: 99%
“…Furthermore, we recently demonstrated that oral ingestion of the dipeptide Ser-Tyr (SY) increases the Tyr content in several brain regions of adult mice more efficiently than administration of Tyr alone at the same intake dose. 8) SY is the most prevalent Tyr-containing dipeptide moiety in several soy proteins. 9) Indeed, SY and other Tyr-containing dipeptides can be detected in their free dipeptide form in the soy peptides used in our in vivo study.…”
Section: Soy Peptide Ingestion Augments the Synthesis And Metabolism mentioning
confidence: 99%
“…Our recent study also demonstrated that oral administration of a dipeptide Ser-Tyr (SY) efficiently increases the free Y content relative to the sole administration of Y alone at the same intake dose in several brain regions of adult mice. 7) This suggests that Y derived from soy proteins/peptides may affect catecholamine metabolism in the brain, since Y can be transported efficiently at the blood-brain barrier and serves as a precursor of catecholamines.…”
mentioning
confidence: 99%
“…Commercially available soybean hydrolysate (Hinute AM) was used in this study, as it is known to contain a number of bioactive dipeptides. These peptides exhibit properties such as in vitro angiotensin I-converting enzyme inhibitory activity (IC 50 : GY, 220 lmol L À1 ; IY, 3.7 lmol L À1 ) (Matsui & Matsumoto, 2006) and improved brain dysregulation effects (SY) (Esaki et al, 2013). Potential interfering effects from the simultaneous detection and quantification of the three targets (GY, IY, and SY) (e.g., overlapped elution and/or suppressed ionization of targets on LC-MS) were considered, and dipeptides with reversed sequences, i.e., YG, YS, and YI, together with LY and YL (having the same molecular weight as target IY), were selected for the study.…”
Section: Introductionmentioning
confidence: 99%